2018
DOI: 10.5213/inj.1835054.527
|View full text |Cite
|
Sign up to set email alerts
|

Lower Urinary Tract Symptoms in Elderly Population With Multiple Sclerosis

Abstract: PurposeThe aim of this study is to compare the clinical and urodynamic characteristics of urinary disorders in multiple sclerosis (MS) patients in a geriatric population with a nongeriatric population.MethodsThis study was conducted retrospectively between 2010 and 2016. Each patient with MS aged 65 and older was matched with 2 patients with MS aged less than 65 in sex, form of MS, and Expended Disability Status Scale (EDSS). Demographic data, urinary symptoms, treatment, quality of life, repercussion of lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…33,34 These findings suggest that aging may exacerbate urinary disorders in MS patients through potentiating pathophysiological factors. 35 According to the current study, LUTS was found to be more common in patients with academic degrees than in those without an academic degree or who were illiterate; however, the difference did not reach statistical significance. In line with our study, an Austrian cross-sectional study found no significant correlation between LUTS and the level of education in men.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…33,34 These findings suggest that aging may exacerbate urinary disorders in MS patients through potentiating pathophysiological factors. 35 According to the current study, LUTS was found to be more common in patients with academic degrees than in those without an academic degree or who were illiterate; however, the difference did not reach statistical significance. In line with our study, an Austrian cross-sectional study found no significant correlation between LUTS and the level of education in men.…”
Section: Discussioncontrasting
confidence: 65%
“… 33 , 34 These findings suggest that aging may exacerbate urinary disorders in MS patients through potentiating pathophysiological factors. 35 …”
Section: Discussionmentioning
confidence: 99%
“…Yet, Koldewijn1995 found that age is not an influencing factor on clinical or urodynamic profile [53]. It could be thinkable that age and MS, by means of potentiation of pathophysiological factors, may increase rate and /or severity of urinary problems in this specific population [54].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst numerous questionnaires on bladder symptoms are available, the USP was chosen as it is a validated questionnaire that incorporates different domains of LUT symptoms and better describes the frequently mixed symptoms experienced by patients with MS. Although not specifically validated in neurological patients, it has been recommended as a screening tool for LUT symptoms in MS [13] and used as an outcome measure in previous studies of patients with MS [14][15][16] and other neurological conditions [17,18]. A ratio of the USP LS/total scores was calculated to account for the degree of voiding LUT symptoms compared to a patient's overall profile of LUT symptoms.…”
Section: Discussionmentioning
confidence: 99%